Prevalence of adverse events and their effect on completion of high speed treadmill exercise tests at a single institution (2000–2015). (25th July 2019) - Brown, K.; Stefanovski, D.; Davidson, E.
Summary: Background: Decline in high speed treadmill (HSTM) exercise testing may be attributed to the rise of over‐ground endoscopy and telemetric electrocardiography, in addition to concerns of adverse events during treadmill exercise resulting in injury or inadequate testing. Objectives: To describe adverse events occurring during HSTM exercise tests at a single institution and determine their effect on likelihood of completing diagnostic HSTM exercise testing. Study design: Retrospective cohort study. Methods: Pearson's chi‐square test was used to determine if a significant difference in frequencies of adverse events existed between complete and incomplete HSTM exercise tests. Two Firth logistic regression models were used to determine likelihood of exercise test completion given the presence of any adverse event, and the likelihood of exercise test completion for each type of adverse event. Results: The majority of horses presenting for HSTM evaluation underwent exercise testing (900/1003; 90%). Eight‐hundred and seven (90%) exercise tests were completed. Adverse events occurred in 136 (15%) HSTM exercise tests of which 97 (71%) did not impact ability to complete HSTM testing. Adverse events significantly but variably decreased the likelihood of HSTM exercise test completion. Sixty‐six percent of incomplete exercise tests were prematurely terminated due to poor performance abnormalities during which diagnosis of poor performance cause(s) was still achieved. Main limitations: Variable personnel recorded data over the study period. Per‐test rather than per‐horse evaluation does not account for the effect of multiple training and testing episodes performed in the same horse. Conclusions: This study supports the continued usage of HSTM exercise testing for examination of horses with poor performance, with adverse events occurring infrequently. Adverse events reduced the likelihood of completing HSTM exercise testing although not all adverse events affected likelihood of completion similarly. In many cases, a performance limiting problem was identified for horses in which an exercise test was considered incomplete. The Summary is available in Spanish – see Supporting information